New Holistic Conceptual Framework for the Assessment of the Performance of Photocatalytic Pavement - Jimenez-Relinque, Eva; Rubiano, Francisco; Hingorani, Ramon; Grande, Maria; Castillo, Angel; Nevshupa, Roman; Castellote, Marta (Frontiers in Chemistry, 2020)
Despite serious health and environmental burdens associated with air pollution by NOx, its ceilings are being systematically exceeded in large European cities since many years. In this context, photocatalytic technology can be an efficient solution for removal of chemical pollutants in air. Being diesel engine exhaust the main source of NOx emission, application of a photocatalyst onto the road pavement appears to be effective for NOx abatement due to the large surface area, proximity to the emission focus, and relatively good solar irradiance. A number of laboratory scale studies provided solid evidences demonstrating that most harmful contaminants can be readily mineralised. Furthermore, several projects were aimed at scaling up this technology to pilot and real scales. Although some of these studies showed photocatalytic performance of selected materials under real urban environment, obtained information is not conclusive for evaluating the overall performance since other material characteristics relevant to its functionality were not assessed. The lack of established conformity criteria suitable for evaluation of the overall performance of photocatalytic pavements under real operational conditions generates scepticism and mistrust among the public authorities and relevant stakeholders that constrains widespread implementation of this promising technology. In this context, the project LIFE+ “Photoscaling” was focused on developing a new holistic conceptual framework for assessing the photocatalytic pavement performance using the decision tool “PhotoScaling Decision Maker” based on a set of quantitative indicators. For this purpose, a large volume of data obtained for ten types of photocatalytic pavement materials on both laboratory scale and the pilot plant platforms were systemized, and three main indicators were defined: 1) Photocatalytic Performance Effectiveness (PPE), 2) Intrinsic performance (IP) and 3: Undesired Secondary Effects (USE). Each top-level indicator includes several low-level sub-indicators associated to specific material characteristics. Finally, the ranges of main indicators and sub-indicators variations and the methods for their assessment were determined. These methods include standard, adopted and original characterization techniques chosen following the criteria of simplicity, cost- and time-effectiveness, and relevance to operational conditions